MILITARY OBJECTIVE AND COLLATERAL DAMAGE: THEIR RELATIONSHIP AND DYNAMICS - Holland, Joseph (Yearbook of international humanitarian law, 2004)
Grisly images of dead or injured civilians vie with ‘morbidly spectacular film of PGM (precision guided munition) strikes’. These phenomena, like this article, focus attention on the two most basic law of targeting components, that of military objective and that of incidental civilian losses. The latter component, being incidental civilian loss, injury and damage, also known as collateral damage, is one side of the proportionality ‘equation’. Expected incidental civilian losses (which term will be used interchangeably with collateral damage) are balanced against the anticipated military value of the strike. This balancing, i.e., proportionality, is one of the major factors in the law of targeting. The concepts examined are two of the most dramatic aspects of targeting. Is there any relationship between military objective and incidental civilian losses? If so, what is the linkage? If one concept expands or contracts what happens to the other? This relationship may have important implications for the type of expertise required to make legal targeting decisions. The type of expertise required would indicate who is best placed to make such targeting decisions and what sorts of errors such decision makers are prone to make and thus must particularly strive to avoid.